INTRA – TRANSFER –SEGMENTAL PRICING,ITS ADAPTABILITY CONCEPT IN DETERMINATION OF ORGANIZATIONAL PROFITABILITY - Ishmael, Omah; Abraham, Ojo Agbodu Ayodele; Babatunde, Adedeji (European Scientific Journal, ESJ, 2012)
Purpose: The purpose of this paper is to highlight the relevance of intra-segmental-transfer-pricing as a measure of interdivisional, interdepartmental performance efficiency, when goods and services are internally transferred within the units in the organization. Methodology/Approach: An empirical survey-based-data collection from TEXLON NIG. PLC (a textile unit with two functional departments –spinning and weaving), Oshodi/Apapa Expressway, Mile 2, Lagos, Nigeria. Findings: Intra-segmental-transfer-pricing basically, is not a market oriented pricing mechanism. The system under which each independent unit has full freedom to negotiate (LAISSEZ FAIRE) is absolutely absent. The segmental pricing by independent units are virtually regulated by guidelines (CENTRALLY IMPOSED). It is a measure of efficiency rather than “Profit performance”. Research Limitations/Implications: i. In intra-segmental-transfer pricing, selling divisions are allowed to recover selling expenses from the user divisions even though no selling expenses are virtually incurred on intra-segmental transfers. ii. The measurement of segmental profit performance is not possible under regulated guidelines (centrally imposed pricing), hence, profit performance of each unit cannot be measured with absolute certainty. Practical Implication: Intra-segmental transfer-pricing is not a measure of divisional profit performance, its utility is limited to internal adaptability scenario. Originality/Value: This paper exhibits more light on the theory/concept of segmental-transfer pricing as a measure of segmental profit performance and its theoretical utility rather than absolute measure of profitability.